Between center-periphery and left-right: A comparison of traditional and new regionalist parties’ strategies in Galicia during the Great Recession - Gómez-Reino, Margarita; Marcos-Marne, Hugo (Revista de Estudios Políticos, 2022)
<span style='text-align: left; color: rgb(0, 0, 0); text-transform: none; text-indent: 0px; letter-spacing: normal; font-family: "Times New Roman", serif; font-size: 15.36px; font-style: normal; font-weight: 400; word-spacing: 0px; float: none; display: inline !important; white-space: normal; orphans: 2; widows: 2; background-color: rgb(240, 243, 250); font-variant-ligatures: normal; font-variant-caps: normal; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;'>This article explains the rise, success, and subsequent failure of new challenger formations in the Galician party system during the Great Recession. For that, it focuses on the multidimensional electoral strategies developed by Alternativa Galega de Esquerda (AGE) and En Marea, comparing them to that of the traditional Bloque Nacionalista Galego (BNG). Our analysis shows the different strategies displayed by the BNG and new challengers (AGE, and later En Marea), examining both the electoral supply (framing and party programmatic positions) and demand (voter positions). We find a new subsuming strategy developed by AGE and En Marea, which prioritized left-wing anti-austerity policies over core pro-periphery ones. The paper demonstrates the potential of this new strategy during the Great Recession but also its limitations, linking its demise to the organizational weakness that prevented electoral realignment, and ultimately allowed the BNG to regain its leading role in the territorial dimension of competition.